Pengembangan Alternatif Pembelajaran Anak-Anak untuk Membentuk Motivasi Belajar pada Masa Pandemi Dusun Mulyasari Desa Padasari - Al-Rosyid, Muhammad Zulfa; Januar , Erik; Yuningsih, Yuyun (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2022)
The Covid-19 pandemic is still ongoing, many sectors are affected by the pandemic. One of them is the education sector which occurs in Mulyasari Hamlet, Padasari Village, Cimalaka District, Sumedang. Learning from home online is considered less effective because the Padasari village area is an area that has difficulty with signal networks and also because it makes students bored and often gets more assignments. In terms of education, the residents of Mulyasari Hamlet, Padasari Village, are still relatively low, this has the potential for a degradation of learning motivation, especially in children. Therefor the authors held an alternative learning program as a means of education for children. The method used is by using certain themes in the implementation of learning and also using nature as a learning tool. One of the supports for learning activities is the formation of study groups. The material presented is part of the material taught in schools but is wrapped in certain themes. From the learning outcomes, participatory monitoring and observation were carried out on children. The results of the monitoring show that there is little change in children from attitudes, language use, self-confidence, interactive learning and an increase in enthusiasm for reading as well as starting to be enthusiastic in religious learning and at least from a cognitive perspective the children’s knowledge increase. Besides this, there are still many obstacles and a complete and comprehensive evaluation is needed because from the results of monitoring not all changes are evenly distributed among children